Kinetic and isotherm study of cupper adsorption from aqueous solution using waste eggshell - Polat, Ayben; Aslan, Sukru (Journal of Environmental Engineering and Landscape Management, 2014)
The sorption of Cu2+ ions from aqueous solutions by eggshell was investigated in a batch experimental system with respect to the temperature, initial Cu2+ concentrations, pH, and biosorbent doses. The adsorption equilibrium was well described by the Langmuir isotherm model with the maximum adsorption capacity of 5.05 mg Cu2+/g eggshell at 25 °C. The value of qe increased with increasing the temperature while also increases the release of Ca2+ and HCO−3 ions from the eggshell. The highest sorption of Cu onto the waste eggshell was determined at the initial pH value of 4.0. The results confirming that the adsorption reaction of Cu2+ on the eggshell was thought to be endothermic. A comparison of the kinetic models such as pseudo first and second-order kinetics, intraparticle diffusion, and Elovich on the sorption rate demonstrated that the system was best described by the pseudo second-order kinetic model.First published online: 19 Mar 2014